Analisis Kemampuan Pemecahan Masalah Siswa SMP pada Materi Statistika Ditinjau dari Kemampuan Awal Matematika - Mega Rosalinda; Santri Chintia Purba; Risma Uli Manalu (Brillo Journal, 2022)
The topic is carried out on the basis of analyzing the math problem solving ability of secondary school students on the basis of statistical documents considered from the initial math problem solving ability. The purpose of this study is to find a method to analyze the math-solving ability of middle school students on the basis of statistical data on the initial math-solving ability. The method used in this study is qualitative method. This study was conducted at Santa Maria Monica High School. Subject used in this study are 9th grade VIII SMP Santa Maria Monica students using rational sampling technique. The results of this study indicate that students with high initial math skills can perform all stages of problem solving correctly and accurately. Students with early average math abilit were able to solve the give problems, were able to take actions to solve the problem, but still the steps were no systematic and not maximal. Students with low initial math skills may not complete all step of the Problem Soving indicator corretly.